Vulgar Verbal Messages on Pete-Pete's Public Transport in Makassar City - Rahim, Abd. Rahman; Munirah, Munirah; Hasrianti, Andi; Yusuf, Nurdin; Arifuddin, Arifuddin; Agus, Muh (Advances In Social Humanities Research, 2024)
The main problem studied in this study is what is the form of eating vulgar language used in land transportation modes? The purpose to be achieved in this study is to describe the form of vulgar language used in the public sector, this research is categorized into qualitative descriptive research types. The subject of this study is public transportation while the data source is all public transportation or land transportation modes in Makassar City. Data collection techniques are carried out through documentation techniques while data analysis is carried out in three stages, namely, data reduction, data classification, and data interpretation. The results of the study showed that the form of using vulgar language in land transportation modes in Makassar City consisted of: 1) Vulgar expressions of very rude categories, 2) Vulgar expressions of rude categories; 3. Medium category vulgar expressions.